Evaluation of the cytotoxic and genotoxic potential of printer toner particles in a 3D air-liquid interface, primary cell-based nasal tissue model. (15th April 2023) - Meyer, Till Jasper; Tekin, Nursen; Hense, Peter; Ehret-Kasemo, Totta; Lodes, Nina; Stöth, Manuel; Ickrath, Pascal; Gehrke, Thomas; Hagen, Rudolf; Dembski, Sofia; Peer, Michael; Steinke, Maria R.; et al.
Abstract: Printer toner particles (TPs) are a common, potentially hazardous substance, with an unclear toxicological impact on the respiratory mucosa. Most of the airways surface is covered by a ciliated respiratory mucosa, therefore appropriate tissue models of the respiratory epithelium with a high in vivo correlation are necessary for in vitro evaluation of airborne pollutants toxicology and the impact on the functional integrity. The aim of this study is the evaluation of TPs toxicology in a human primary cell-based air-liquid-interface (ALI) model of respiratory mucosa. The TPs were analyzed and characterized by scanning electron microscopy, pyrolysis and X-ray fluorescence spectrometry. ALI models of 10 patients were created using the epithelial cells and fibroblasts derived from nasal mucosa samples. TPs were applied to the ALI models via a modified Vitrocell® cloud and submerged in the dosing 0.89 – 892.96 µg/ cm 2 . Particle exposure and intracellular distribution were evaluated by electron microscopy. The MTT assay and the comet assay were used to investigate cytotoxicity and genotoxicity, respectively. The used TPs showed an average particle size of 3 – 8 µm. Mainly carbon, hydrogen, silicon, nitrogen, tin, benzene and benzene derivates were detected as chemical ingredients. By histomorphology and electron microscopy we observed the development of a highly functional, pseudostratified epithelium with a continuous layer of cilia. Using electron microscopy, TPs could be detected on the cilia surface and also intracellularly. Cytotoxicity was detected from 9 µg/ cm 2 and higher, but no genotoxicity after ALI and submerged exposure. The ALI with primary nasal cells represents a highly functional model of the respiratory epithelium in terms of histomorphology and mucociliary differentiation. The toxicological results indicate a weak TP-concentration-dependent cytotoxicity. Availability of data and materials: The datasets used and analysed during the current study are available from the corresponding author on reasonable request. Highlights: Mucosa model based on primary cells resembles the situation in vivo. Visualization of cell-particle interaction at the ultrastructural level. Printer toner particle SEM-analysis showed particle diameters of 3 – 8 µm. Toner particles induce concentration-dependent cytotoxicity, but no genotoxicity.